Eutrephoceras subplicatum (Steinmann, 1895) is a junior synonym of Eutrephoceras dorbignyanum (Forbes in Darwin, 1846) (Cephalopoda, Nautiloidea) from the Maastrichtian Quiriquina Formation of Chile - Nielsen, Sven; Salazar Soto, Christian (Cretaceous research, 2011)
Nautilus subplicatus Steinmann, 1895 is a latest Cretaceous species of nautiloid which is common in southern South America (Chile, Argentina) and the Antarctic Peninsula and which is best assigned to the genus Eutrephoceras Hyatt, 1894. Nautilus dorbignyanus Forbes in Darwin, 1846 and Nautilus valenciennii Hupé in Gay, 1854 are here considered to be senior synonyms which later authors have apparently overlooked. The type material of these two taxa is reillustrated. On the basis of this and additional material it is demonstrated that only a single nautiloid species occurs in the Quiriquina Formation of late Maastrichtian age. For this we propose to use N. dorbignyanus as the oldest available name.
Gesehen am 28.09.2022